1997
DOI: 10.1093/humrep/12.4.651
|View full text |Cite
|
Sign up to set email alerts
|

Tissue renin-angiotensin systems and reproduction

Abstract: The continued acquisition of information on the distribution of expression of components of the renin-angiotensin system shows that it has functions in the tissues that are quite unrelated to its systemic actions. In particular, both type 1 and type 2 angiotensin receptors are found in many tissues of the reproductive system of both sexes. In addition, the widespread occurrence of (pro)renin, angiotensin converting enzyme and angiotensinogen suggests that the generation of angiotensin II within the tissues occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 16 publications
3
66
0
2
Order By: Relevance
“…All tissues were stained with the lectin Bandeirae simplicifolia (red) to visualise blood vessels within the pancreatic islets. Scale bar=50 μm effects [17][18][19][20][21][22][23][24]. The best known functions of angiotensin II, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All tissues were stained with the lectin Bandeirae simplicifolia (red) to visualise blood vessels within the pancreatic islets. Scale bar=50 μm effects [17][18][19][20][21][22][23][24]. The best known functions of angiotensin II, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…3 Vascular density in native mouse pancreatic islets and in islet grafts 4 weeks after transplantation beneath the renal capsule of syngeneic C57BL/6 mice. Some of the transplanted animals were subjected to treatment with the angiotensin II type 1 receptor inhibitor losartan (30 mg·kg −1 ·day −1 ) dissolved in the drinking water throughout the 4-week post-transplantation period (days 0-28) or for the final 14 days (days [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Values are given for the endocrine tissue (closed bars), the connective tissue stroma (hatched bars) and the whole islet graft (empty bars).…”
Section: Graft Insulin Release and Insulin Contentsmentioning
confidence: 99%
“…Although the peptide angiotensin II (AII) is generally known for its roles in regulating cardiovascular and electrolyte homeostasis (Vinson et al 1997), AII is also found in seminal plasma at concentrations higher than in blood (O'Mahony et al 2000). This suggests that AII might be able to act on mammalian spermatozoa, in addition to other somatic cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Although the responses to FPP and calcitonin appear to involve G protein-mediated regulation of AC activity, the precise mechanism by which AII is able to stimulate cAMP production remains unclear. The AT1 receptor for AII belongs to the G protein-coupled receptor family (Vinson et al 1997). In somatic cells, AT1 receptors are usually linked to Ga q -containing G proteins; consequently, AII stimulation is often linked with phospholipase C activation, resulting in increased generation of diacylglycerol and inositol trisphosphate, activation of protein kinase C (PKC) and elevated intracellular Ca 2þ concentration (Sayeski et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II (AII) is an octapeptide (Asp-Arg-Val-TyrIle-His-Pro-Phe) widely known for its roles in regulating cardiovascular and electrolyte homeostasis (see review by Vinson et al 1997). However, AII is also found in seminal plasma at concentrations higher than in blood plasma (O'Mahony et al 2000) and there is evidence that AII receptors of subtype 1 (AT1) are present on mammalian spermatozoa (Vinson et al 1995, Gur et al 1998, Wennemuth et al 1999).…”
Section: Introductionmentioning
confidence: 99%